Pengaruh Motivasi Belajar, Efikasi Diri, dan Teman Sebaya Terhadap Kemandirian Belajar Akuntansi Mahasiswa Pendidikan Akuntansi Universitas Negeri Surabaya - Dwi Anugrah Marthadiningrum; Irin Widayati (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2022)
Self-regulated learning is an important aspect in learning, especially self-regulated learning of accounting. But in reality, students often lose their self-regulated learning when facing difficulties in their learning activities. Researcher conducted this study in order to determine and examine the influence of learning motivation, self-efficacy, and peers on self-regulated learning of accounting, either simultaneously and partially. This study was classified as causality research with quantitative approach. The population in this study were students of Accounting Education 2018-2019, State University of Surabaya, totaling 116 students. Proportional random sampling method, the researcher used as a sampling technique to obtain a sample of 90 respondents. Research data was collected through the distribution of questionnaires. Hypothesis testing was done by using multiple linear regression method. The results of this research analysis concluded: 1) Learning motivation with tcount = 7,791 > ttable = 1,988 affected self-regulated learning of accounting, 2) Self-efficacy with tcount = 2,043 > ttable = 1,988 affected self-regulated learning of accounting, 3) Peers with tcount = 3,173 > ttable = 1,988 affected self-regulated learning of accounting, 4) Learning motivation, self-efficacy, and peers with Fcount = 59,255 > Ftable = 8,558 simultaneously affected self-regulated learning of accounting.